Profesor dan Doktor bagi Politisi: Sebuah Tinjauan Filosofis Tentang Gelar Akademik dalam Perspektif Relasi Kapital Pierre Bourdieu - Eka Putra, Surya Desismansyah (Universitas Negeri Malang, 2025)
This study aims to analyze the essence of professor and doctoral degrees in academia and the relationship of academic degrees as a capital commodity favored by politicians from Pierre Bourdieu’s perspective. The method in this study is a literature study carried out systematically through the stages of topic identification, collection of relevant literature, critical analysis of content, and compilation of results in a narrative framework. Data were collected from various sources such as journal articles, books, and relevant academic documents. Data analysis was carried out by deeply examining the arguments in the literature. The results of the study show that doctoral and professorial degrees are ethical achievements awarded by higher education institutions to individuals after meeting academic and pedagogical standards. Academic degrees have now become economic commodities for politicians to perpetuate domination. Academic degrees based on Pierre Bourdieu’s perspective can be understood as a form of symbolic capital that is often used to strengthen positions in social and political structures. The commodification of degrees not only reduces the intrinsic value of academic degrees, but also reduces public trust in the higher education system.